Analisis Efisiensi Usahatani Padi di Kabupaten Lampung Tengah - Budi Yoko; Yusman Syaukat; Anna Fariyanti (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2014)
An effort to increase rice production through agricultural extension in Central Lampung regency is difficult. This is because of the limited land that can be used as new planning areas and high competition for land use as non-agricultural activities. Therefore, the increase in rice production through production efficiency becomes the most important alternative. The objectives of this study are to analyze the level of technical efficiency, allocative efficiency, and economic efficiency of rice farming in Central Lampung district and identified the factors that influence it. The results of the analysis using stochastic frontier production function shows that rice farming in the study area has been efficient. Average efficiency level of technical efficiency is 0,94, allocative efficiency is 0,93, and economic efficiency is 0,88. The land area is the most responsive variable in an effort to increase rice production. Variables expected to affect the degree of technical efficiency of rice farming is the number of family members of farmers, rice farming experience, acces farmers to agricultural financing, and number of agricultural extension.